Dehydrogenation and spheroidization of titanium hydride powder based on fluidization principle. Issue 1 (2nd January 2020) - Zheng, Yan; Zhang, Jingfan; Liu, Yue; Jia, Shizhao; Tang, Ruolan; Zhang, Deliang
ABSTRACT: Dehydrogenation of TiH2 powder is an important method for preparing low-cost titanium powder. In this study, a novel dehydrogenation process of titanium hydride powder was developed based on the fluidization principle. TiH2 powder with particle sizes of <75 μm was placed evenly on the fluidization bed in a specially designed reactor and dehydrogenated at 560°C for 120 min with argon gas flowing from the bottom to top of the reactor. The resulting powder was analyzed using X-ray diffractometry, scanning electron microscopy, Hall flowmeter and laser scattering particle size analyzer. It was evident that a Ti powder with a small amount of TiH1.5 was obtained after the dehydrogenation process at a relatively low temperature. The edges and corners of the particles became rounded due to the thermodynamic driving force originated from the reduction of particle surface areas. The fluidity of powder was also improved due to the increase of sphericity of the powder particles during dehydrogenation. After dehydrogenation, the particle size range became smaller, and the average particle size increased, showing that slight sintering of the very fine titanium particles occurs.